Qalbun Salīm and the Development of Islamic Character: A ‎Comparison of Sya'rawi’s and Ruh Al-Ma'ani’s Exegeses - Deki Ridho Adi Anggara; Asif Trisnani; Wahyu Septrianto; Siti Sarah Shahifah (Jurnal Ulunnuha, 2026)
In the modern era, moral crises and character degradation require strengthening the spiritual ‎dimension of Islamic education. One Qur’anic concept relevant to addressing this challenge ‎is qalbun salīm (a sound heart). This study aims to analyse the concept of qalbun salīm through ‎a comparative examination of the interpretations of Muhammad Mutawalli al-Sya‘rawi in ‎Tafsir al-Sya‘rawi and Mahmud al-Alusi in Tafsir Ruh al-Ma‘ani, as well as its implications for ‎Islamic character formation. This study is a qualitative, literature-based research (library ‎research). The primary data sources are Tafsir al-Sya‘rawi and Tafsir Ruh al-Ma‘ani, whilst the ‎data is analysed using comparative and content analysis methods. The results of the study ‎indicate that both exegetes interpret qalbun salīm as a heart free from shirk, hypocrisy, and ‎various diseases of the heart. The difference lies in the fact that al-Sya‘rawi places greater ‎emphasis on the aspects of human nature, faith, and social relevance in character formation, ‎whilst al-Alusi highlights the spiritual dimension, tazkiyatun nafs, and the purification of the ‎heart from various inner ailments. These findings indicate that qalbun salīm is a crucial ‎foundation in the formation of Islamic character through the strengthening of faith, the ‎control of desires, and the cultivation of righteous deeds. The integration of these two ‎perspectives yields a more comprehensive approach to the development of Islamic character ‎education that balances the aspects of faith, morality, and spirituality.‎